DETERMINANTS OF A FUNCTIONAL REFERRAL SYSTEM IN KISUMU COUNTY, KENYA PATIENTS' PERSPECTIVE - Nango, Otieno Wilbert; Mwangi, Ms. Eunice Muthoni; Oluoch, Mr. Musa (Global Journal of Health Sciences, 2019)
Purpose: Most referral health facilities are faced with challenges ranging from congestion of patients at these health facilities, strained/ limited resources (both human and material) to deal with the voluminous patients, slow rate of service delivery to the patients which normally results in compromised quality of medical care provided to the patients. The study therefore aimed to find out the determinants of a functional referral system in two high level health facilities; Jaramogi Oginga Odinga Referral Hospital (JOOTRH) and Kisumu County Referral Hospital (KCH). Methodology: A cross sectional study was conducted using a quantitative approach to data collection. Three hundred and thirty eight out-patient clients were systemically selected to participate in the study. Data was collected using Individual questionnaire. The collected quantitative data were coded and analyzed using the SPSS 25.0 Computer program. The quantitative data were then analyzed using the descriptive statistics and logistic regression models. Results: The research findings revealed that there is a positive significant correlation between primary health facility characteristics (r = 0.474**; P<0.000).It also revealed that there is a positive significant correlation between receiving facility characteristics (r = 0.475**; P<0.000) to a functional referral system. Further Multivariate analysis also revealed a significant association between referral health facility characteristics and a functional referral system, (Î²3 = .425, P =.000).The results further revealed that there was a negative significant association between receiving health facility characteristics and a functional referral system, (Î²4 =.-0.156, P < .000). Unique Contribution to Theory, Practice and Policy: The County government of Kisumu should supply adequate drugs and equipment's to attract more patients seeking medical care services to the primary level facilities. Quality of services offered and general cleanliness at the primary health facilities should also be improved to boost patient's confidence in them.